The COVID-19 pandemic: A threat to higher education? - Marina Bonaccolto-Töpfer; Carolina Castagnetti (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2021)
Transition to online teaching during the first wave of the COVID-19 pandemic has led to various concerns about educational quality. So far, researchers have mainly focused on the effects on school teaching. This paper looks at the effects on a large Italian university (University of Pavia, Lombardy). Administrative data allows us to track both students' evaluation of teaching and student performance. Using a difference-in-differences design, we exploit the fact that the summer term 2020 started right after the first lockdown and compare students' outcome during this term to those of the same term in the previous year. In contrast to the literature, our results suggest no substantial effects of the pandemic on higher education. The findings are robust across various dimensions of courses, students and lecturers. In particular, the results suggest also no difference between top and bottom students or students from wealthier and poorer families. – – Der Übergang zur Online-Lehre während der erstenWelle der COVID-19-Pandemie hat zu Sorgen über die Qualität der Lehre geführt. Bisher hat sich die Forschung größtenteils auf Effekte der Pandemie auf Schulen konzentriert. Dieses Papier analysiert die Auswirkungen auf eine große italienische Universität (Universität Pavia, Lombardei). Administrative Daten erlauben es uns, sowohl die Evaluation der Lehre als auch die Leistung von Studierenden zu betrachten. Mittels eines Differenz-von-Differenzen Ansatzes verwenden wir die Tatsache, dass das Sommersemester 2020 direkt nach dem ersten Lockdown gestartet ist, und vergleichen Ergebnisse von Studierenden in diesem Semester mit denen im gleichen Semester des vorangegangenen Jahres. Anders als die Literatur finden wir keine substanziellen Effekte der Pandemie auf Hochschulbildung. Unsere Ergebnisse sind entlang diverser Kurs-, Studierenden- und Dozierenden-Dimensionen robust. Insbesondere suggerieren die Ergebnisse auch keine Unterschiede zwischen sehr guten und schwachen Studierenden oder zwischen Studierenden aus reicheren und ärmeren Familien.
Keywords: G18; I18; I23; I24; 330; Online teaching; COVID-19 pandemic; difference-in-differences; higher education